Meningkatkan Kemampuan Pemahaman Konsep Matematika Melalui Model Pembelajaran Experiental Learning Siswa Kelas IV Sekolah Dasar - -, Nurhaswinda; -, joni; Rohani, Putri (el-Ibtidaiy:Journal of Primary Education, 2024)
The background of this research is the low ability to understand mathematical concepts in grade IV students. This research aims to improve students' conceptual understanding abilities in class IV UPT SDN 013 Kumantan. This research is a class follow-up research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this research were 1 teacher and 6 students, while the object was to use the Experiential Learning model to improve students' conceptual understanding skills. The research instrument consisted of teacher activity observation sheets, student activity observation sheets, documentation sheets and study test sheets during the learning process using the Experiential Learning learning model. While the data analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, the test results obtained in cycle I meeting 1 were 64.5 with classical completeness 37.5% and meeting 2 79.75 with classical completeness 62.5%, while in cycle II meeting 1 the results obtained were 78, 12 with 75% classical completeness while the 2nd meeting obtained 84.25 results with 87.5% classical completeness. Based on the results of this research, it shows that by using the Experiential Learning learning model, it can improve the ability to understand mathematical concepts in class IV UPT SDN 013 Kumantan.